Model Manajemen Strategi CSR dalam Industri Kelapa Sawit Berkelanjutan (PTPN IV Unit Usaha Adolina) - Tarigan, Sidik; Siregar, M. Akbar; Siahaan, Elisabeth (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2021)
The average CSR development in PTPN-IV Adolina Business Unit has increased every year with a larger budget and realization. This study aims to determine the success factors of CSR which have a significant effect on the sustainability of oil palm companies, the elements that form a sustainable palm oil industry, the effect of good CSR implementation on the sustainability of the palm oil industry, building a CSR-based strategic management model towards the palm oil industry. sustainable. This research method uses descriptive quantitative research methods with a total sample of 102 people. The types of data used are primary data and secondary data. Primary data were collected through a questionnaire measured through a Likert scale and secondary data through documentation studies. The data was processed with SPSS 20.0 for Windows software. Hypothesis testing uses Multiple Regression Analysis. Research to see the effect of corporate commitment, operational standard CSR internalization policies, involving the community on the implementation of CSR in the oil palm sector of PTPN IV Kebun Adolina. The results of this study concluded that company commitment, CSR internalization policies in operational standards and involving local communities, have a significant positive effect on CSR implementation, where the most significant positive effect is first involving local communities, then CSR internalization policies in operational standards and then corporate commitment companies towards the implementation of CSR in the oil palm sector at PTPN IV Kebun Adolina.